PHILOSOPHICAL VIEWS OF RENE DEKART IN THE WORK “THE FIRST PHILOSOPHY” - Mamaroziqov Azizjon Davronovich (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
He was also instrumental in the development of philosophical thought. Descartes was dualistic in his philosophical views. According to him, the basis of the universe is intangible and material substance. Both were created by a higher substance, God. However, the human mind thought it was incapable of knowing. Descartes is a philosopher who has left a special place in the history of philosophy.